2019
DOI: 10.1101/786533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Light-Inducible Recombinases for Bacterial Optogenetics

Abstract: Optogenetic tools can provide direct and programmable control of gene expression. Lightinducible recombinases, in particular, offer a powerful method for achieving precise spatiotemporal control of DNA modification. However, to-date this technology has been largely limited to eukaryotic systems. Here, we develop optogenetic recombinases for Escherichia coli which activate in response to blue light. Our approach uses a split recombinase coupled with photodimers, where blue light brings the split protein togethe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…1c). As the light-triggered dimerization domain we selected VVD, which has often been successfully employed to control with light the dimerization of proteins of interest 5,6,13,14 . VVD senses blue light via the flavin adenine di-nucleotide (FAD) chromophore 10 .…”
Section: Creation Of a Small Library Of Chimeric Vvd-arac Fusion Consmentioning
confidence: 99%
“…1c). As the light-triggered dimerization domain we selected VVD, which has often been successfully employed to control with light the dimerization of proteins of interest 5,6,13,14 . VVD senses blue light via the flavin adenine di-nucleotide (FAD) chromophore 10 .…”
Section: Creation Of a Small Library Of Chimeric Vvd-arac Fusion Consmentioning
confidence: 99%
“…Although the potential of our computational results remains to be verified through independent experimental investigation, we believe that this numerical demonstration of the potential for a new control paradigm not only opens new possibilities for integrated "cyber organic" approaches in synthetic biology [28][29][30]45 but also could offer insight into natural cellular differentiation processes where cellular states are sensed, and control signals are transmitted, by neighboring cells. For example, it has been suggested that stochastic fluctuations in expression lead embryonic stem cells to achieve substantial and functionally relevant heterogeneity in Nanog expression, where transiently low Nanog expression cells are prone toward differentiation, whereas high Nanog expression cells are less likely to differentiate.…”
Section: ■ Conclusionmentioning
confidence: 83%
“…When coupled to advances in microfluidics, these capabilities introduce a new part-biology-part-machine (or cyber-organic 27 ) paradigm that adds new possibilities for distributed external and internal biological control of synthetic biological circuits. 28 In particular, recent developments in optogenetics 29,30 have greatly increased the speed and sensitivity by which external signals can be communicated from humans or machines to cells. Using these advances in microfluidics and light-activated gene regulatory elements rapidly improves the potential to integrate carbon-and silicon-based circuits, which in turn makes hybrid bioelectronic circuits far more powerful than before.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Other emerging tools have the potential for refined time-varying control of gene expression in microbes. For example, inducible CRISPR activation/inhibition systems [67,68], photoactivatable recombinases [69,70], and electronic-based control [71][72][73] can be applied to perturb endogenous pathways within physiologically relevant ranges. Additionally, inducible asymmetric cell division systems offer unique capabilities for investigating mechanisms linked to phenotypic variation, such as the recently reported unequal partitioning of efflux pumps in bacteria [25••].…”
Section: Spatio-temporal Control Of Gene Expressionmentioning
confidence: 99%